Sistem Pencatatan dan Pengolahan Keuangan Pada Aplikasi Manajemen Keuangan E-Dompet Berbasis Android - juhardi, ujang; Khairullah, Khairullah (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2019)
Abstract— The way to achieve a more prosperous person is to control his finances wisely and carefully. One effort that can be done is to make a financial record so that finances can be well controlled. Such financial records can help a person to stay in stable financial condition so as to be able to see whether there should be a reduced expenditure or additional savings. But in general the recording of financial statements are still done manually, namely by way of recording transactions to the notebook and manually calculate the transaction data so as to produce financial statements in a simple bookkeeping. However, it is very inefficient, the large number of transactions that occur every day requires that recording, transaction counting and reporting take some time. From these problems then the authors will discuss How Making Recording System and Financial Processing In Application Management Finance e-Wallet Based Android. So the benefits of this research is to facilitate and assist a person in recording, calculating and managing income and financial expenditure using an Android-based mobile device. This research is independentKeywords: System, Financial Management, e-Dompet